Eficiência fotossintética nos manguezais na Baía de Vitória, ES - Pascoalini, Sávia Soares (2014)
The mangrove species have different mechanisms to eliminate the salt. Some of them are salt secretors species and others salt accumulators. These mechanisms give them to increase tolerance to salinity, as Avicennia schaueriana Stapf & Leechman ex Moldenke and Laguncularia racemosa (L.) Gaertn, respectively. In contrast, excluders salt species that do this on the root level, such as Rhizophora mangle L. are more sensitive to the effects of salts. In this sense, our aim is to evaluate how was the behavioral to the most tolerant species in photosynthetic efficiency under different salinities and if such species will exhibit higher photosynthetic efficiency at higher salinities. Two mangrove areas, under different salinity conditions were chosen for the study, mangrove of Baleia Island (20.91 ± 1.25) and Aribiri River (27.13 ± 2.91), located in the Bay Vitoria, ES. A. schaueriana and L. racemosa had higher quantum yield of primary photochemistry – 0.90 (f P0) in Baleia Island. However, the highest values of the Performance Index by absorption (PI ABS) were observed in L. racemosa and R. mangle, 2.40 and 2.33, respectively. The total Performance Index (PI total) was higher in L. racemosa, 2.25. However, carbon assimilation (A) did not differ statistically among the species assessed. In Aribiri river, L. racemosa and R. mangle feature the best photochemical performance as seen in the parameters f Po ( 0.91 ), PI ABS (2.48) and total PI (2.20 and 2.33). However, the evaluation of gas exchange indicates that A. racemosa and L. schaueriana are more tolerant to salt conditions as originally conjectured, both have higher A (1.15 and 1.07) and Water Use Efficiency (WUE) Intrinsic (2.22 and 2.36) and Instantaneous (1.19 and 1.14), respectively. R. mangle demonstrates to be sensitivity to salinity when we analyze its carbon assimilation and WUE.